Role of Technology Proficiency, Self-Confidence, and Entrepreneurial Orientation in Enhancing Self-Motivation and Performance of Female MSME Employees in North Luwu - Basir, Nur Halifah; Hamid, Rahmad Solling; Duriani, Duriani (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study explores the impact of technology proficiency, self-confidence, and entrepreneurial orientation on self-motivation and performance of female MSME employees. Methodology: Quantitative analysis of 240 respondents using PLS-SEM. Results and Findings: Technology proficiency significantly affects self-motivation but not directly performance. Self-confidence positively impacts both self-motivation and performance. Entrepreneurial orientation affects self-motivation but not directly performance. Self-motivation mediates the relationship between entrepreneurial orientation, technological proficiency, and self-confidence with employee performance. Novelty and Originality: The study introduces a model linking digital proficiency with motivational and performance outcomes among female MSME employees, a relatively unexplored area. Conclusion: Self-motivation is a crucial mediating factor, emphasizing the need for technological training and confidence-building initiatives. Type of Paper: Empirical research article.